Nurses’ Widespread Job Dissatisfaction, Burnout, And Frustration With Health Benefits Signal Problems For Patient Care - McHugh, Matthew D. (2011)
Job dissatisfaction among nurses contributes to costly labor disputes, turnover, and risk to patients. Examining survey data from 95,499 nurses, we found much higher job dissatisfaction and burnout among nurses who were directly caring for patients in hospitals and nursing homes than among nurses working in other jobs or settings, such as the pharmaceutical industry. Strikingly, nurses are particularly dissatisfied with their health benefits, which highlights the need for a benefits review to make nurses’ benefits more comparable to those of other white-collar employees. Patient satisfaction levels are lower in hospitals with more nurses who are dissatisfied or burned out—a finding that signals problems with quality of care. Improving nurses’ working conditions may improve both nurses’ and patients’ satisfaction as well as the quality of care.